Freewheel Training Alters Mouse Hippocampal Cytokines - Pervaiz, N.; Hoffman-Goetz, L. (International Journal of Sports Medicine, 2011)
The effects of 16 weeks of voluntary wheel running in healthy female mice on hippocampal expression of pro-(TNF-α, IL-1β, IL-12) and anti-(IL-10, IL-1ra) inflammatory and pleiotropic (IL-6) cytokines and apoptotic status of specific cell subsets (CD45+, CD11b+) were studied. Mice were assigned to wheel running (WR; n=20) or a control condition (No WR; n=22) and sacrificed after the 16 weeks. Data collected included measures of training status (running volume, body weight, run-to-exhaustion time, and skeletal muscle cytochrome c oxidase activity), flow cytometric analysis of cell phenotypes and apoptosis (CD45+, CD11b+, Annexin+, Annexin+/PI+, PI+), and cytokine concentrations in cell lysates. WR mice had measurable training effects and significantly lower TNF-α (p<0.05) and higher IL-6 (p<0.05), IL-1ra (p<0.05) and IL-12 (p<0.05) expression in the hippocampus compared to controls. IL-1β, IL-10, and the percent of apoptotic and dead cells did not change due to training. Taken together, and in relation to the complex interactions between cytokines, the results suggest a possible mechanism whereby exercise training may buffer from dementia and cognitive decline through changes in the central cytokine milieu in the hippocampus.
Keywords: voluntary exercise; hippocampus; microglia; TNF-α; IL-6; IL-1ra